Controlling individuals growth in semantic genetic programming through elitist replacement - Castelli, Mauro (2016)
Castelli, M., Vanneschi, L., & Popovič, A. (2016). Controlling individuals growth in semantic genetic programming through elitist replacement. Computational Intelligence And Neuroscience, 2016, [8326760]. https://doi.org/10.1155/2016/8326760